The computational view of information privacy enhancing technologies - Skinner, Geoffrey; Han, Song; Chang, Elizabeth (CompLex, 2006)
Information privacy is a very subjective and context sensitive area of research open to many interpretations. As such it has seen an increasing number of solutions proposed that address the issue of privacy protection. What is missing is a way of classifying the level of protection these privacy protecting solutions provide. This paper addresses this problem by firstly defining the computational view of Information Privacy. Within this view three levels of privacy protection are defined and applied to a number of Privacy Enhancing Technologies that are in use today or in current development. The paper is aimed at providing a unique proposal for terminology that can be utilized in the information privacy field to categorize privacy protecting solutions.